Dynamically Navigated versus Freehand Access Cavity Preparation: A Comparative Study on Substance Loss Using Simulated Calcified Canals - Jain, Sameer D.; Saunders, Madison W.; Carrico, Caroline K.; Jadhav, Aniket; Deeb, Janina Golob; Myers, Garry L. (Journal of endodontics, 2020)
The aim of this in vitro study was to compare the speed, qualitative precision, and quantitative loss of tooth structure with freehand and dynamically navigated access preparation techniques for root canal location in 3-dimensional–printed teeth with simulated calcified root canals. Forty maxillary and mandibular central incisors (tooth #9 and tooth #25) were 3-dimensionally printed to simulate canal calcification. Under simulated clinical conditions, access preparations were randomly performed with contemporary freehand and dynamically navigated techniques. Qualitative precision and quantitative loss of tooth structure were assessed on postoperative cone-beam computed tomographic scans using ITK-SNAP open-source segmentation (http://www.itksnap.org/). The associations between jaw, technique, volume of substance loss, and operating time were determined using analysis of variance models with Tukey-adjusted post hoc pair-wise comparisons. The kappa statistic was used to determine agreement between 2 independent, blinded raters on the qualitative assessment of the drill path. The association between the technique and jaw and qualitative assessment scoring was compared using the Fisher exact test. The significance level was set at .05. Dynamically navigated accesses resulted in significantly less mean substance loss in comparison with the freehand technique (27.2 vs 40.7 mm3, P < .05). Dynamically navigated accesses were also associated with higher optimal precision (drill path centered) to locate calcified canals in comparison with the freehand technique (75% vs 45%, P > .05). Mandibular teeth were associated with a negligible difference in substance loss between the access techniques (19.0 vs 19.1 mm3, P > .05). However, qualitatively the freehand technique was still prone to 30% higher chance of suboptimal precision (drill path tangentially transported) in locating calcified canals. Overall, dynamically navigated accesses were prepared significantly faster than freehand preparations (2.2 vs 7.06 minutes, P < .05). Within the limitations of this in vitro study, overall dynamically navigated access preparations led to significantly less mean substance loss with optimal and efficient precision in locating simulated anterior calcified root canals in comparison with freehand access preparations.